Exploring the Macro and Micro contextual factors influencing the entrepreneurial journey of women in high growth male dominated sectors in India - Bajaj, Sakshi (2014)
Women entrepreneurs have been recognized as one of the most underutilized resource for economic growth in India (Vinothalakshmi and Ganesan, 2013). While the representation of women entrepreneurs is generally low, the numbers are even lower in high growth male dominated sectors like science, engineering, technology, judiciary etc. This study is based on women entrepreneurs within male dominated industries in India that have successfully been running their own venture. It explores the macro and micro contextual factors including, the role of socio-cultural factors; financial institutions; individual social networks and human capital, which influence the venture formation and growth of women owned businesses. Adopting a qualitative research methodology, this study interviews nine women entrepreneurs in masculine sectors of the industry including biotechnology, law, architecture, consultancy, technology and science. The research identifies family support, informal social networks, education and experience to play a critical role in accelerating the formation and growth of women owned entrepreneurial ventures; it also establishes financial institutions and the traditional gendered norms and mentality of the Indian society to be the major factors impeding the growth of women owned businesses in India. The research paper also identifies various coping mechanisms adopted by women entrepreneurs to fit in within the masculine domains.